2014
DOI: 10.1111/epi.12562
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique of detectingMRI‐negative lesion in focal symptomatic epilepsy: IntraoperativeShearWaveElastography

Abstract: SUMMARYFocal symptomatic epilepsy is the most common form of epilepsy that can often be cured with surgery. A small proportion of patients with focal symptomatic epilepsy do not have identifiable lesions on magnetic resonance imaging (MRI). The most common pathology in this group is type II focal cortical dysplasia (FCD), which is a subtype of malformative brain lesion associated with medication-resistant epilepsy. We present a patient with MRI-negative focal symptomatic epilepsy who underwent invasive electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 14 publications
(16 reference statements)
1
30
0
3
Order By: Relevance
“…Using SWE, Chan et al (2014) revealed a focal area of increased stiffness approximately 1.5 cm from the brain surface (Fig. 1E) on a 7 year old boy presented with a 5 year history of medication-resistant frontal lobe epilepsy.…”
Section: Ex Vivo Brainmentioning
confidence: 99%
“…Using SWE, Chan et al (2014) revealed a focal area of increased stiffness approximately 1.5 cm from the brain surface (Fig. 1E) on a 7 year old boy presented with a 5 year history of medication-resistant frontal lobe epilepsy.…”
Section: Ex Vivo Brainmentioning
confidence: 99%
“…7,32 In addition to traditional intraoperative CT and MRI, further technologies such as advanced intraoperative ultrasonography and intraoperative elasticity imaging may better aid in real-time identification of dysplastic lesions and in more accurate depiction of margins. 5,18 Furthermore, intraoperative ultrasonography has been shown to successfully integrate with functional MRI and DTI to provide an intraoperative update to neuronavigation accounting for brain shift. 26 While we found iMRI to be a powerful addition to preexisting epilepsy protocol techniques, its resolution is limited to approximately 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The adult thyroid has been extensively examined by US techniques [9,[67][68][69][70][71][72] but little is known for the use of US elastography in pediatric patients [73].…”
Section: Spleenmentioning
confidence: 99%